C-reactive protein is related to a distinct set of alterations in resting-state functional connectivity contributing to a differential pathophysiology of major depressive disorder. (April 2022) - Beckmann, Fienne-Elisa; Seidenbecher, Stephanie; Metzger, Coraline D; Gescher, Dorothee M; Carballedo, Angela; Tozzi, Leonardo; O'Keane, Veronica; Frodl, Thomas
Highlights: Dysregulated neuronal circuits are related to inflammation in MDD. Inflammation is linked to dysregulation between affective and default mode network. Depression is associated with increased resting state functional connectivity. Findings support the hypothesis of an immune inflammatory subtype of depression. Abstract: Background: Several studies in major depressive disorder (MDD) have found inflammation, especially C-reactive protein (CRP), to be consistently associated with MDD and network dysfunction. The aim was to investigate whether CRP is linked to a distinct set of resting-state functional connectivity (RSFC) alterations. Methods: For this reason, we investigated the effects of diagnosis and elevated blood plasma CRP levels on the RSFC in 63 participants (40 females, mean age 31.4 years) of which were 27 patients with a primary diagnosis of MDD and 36 healthy control-subjects (HC), utilizing a seed-based approach within five well-established RSFC networks obtained using fMRI. Results: Of the ten network pairs examined, five showed increased between-network RSFC-values unambiguously connected either to a diagnosis of MDD or elevated CRP levels. For elevated CRP levels, increased RSFC between DMN and AN was found. Patients showed increased RSFC within DMN areas and between the DMN and ECN and VAN, ECN and AN and AN and DAN. Conclusions: The results of this study show dysregulated neural circuits specifically connected to elevated plasma CRP levels and independent of other alterations of RSFC in MDD. This dysfunction in neural circuits might in turn result in a certain immune-inflammatory subtype of MDD.